Chemical composition of the essential oils of Anethum graveolens L. (Bangladesh Journal of Botany, 2015)
The volatile constituents of the leaves of Anethum graveolens L., growing wild in Iran, were investigated by GC/MS, ?-Phellandrene (29.12%), limonene (26.34%), dill ether (15.23%), ?-pinene (2%), n-tetracosane (1.54%), sabinene (1.34%), neophytadiene (1.43%), n-docosane (1.04), n-tricosane (1%), n-nonadecane (1%), n-eicosane (0.78%), n-heneicosane (0.67%), ?-myrcene (0.23%) and ?-tujene (0.21%) were found to be the major constituents of the oil. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22742 Bangladesh J. Bot. 44(1): 159-161, 2015 (March)